The Classroom Environment and its relation to Classroom Discipline from the View Point of Teachers - A Field Study in the Second Cycle Schools of Basic Education In Lattakia city - مبيّض , مهند محمد (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
This research aimed to identify the reality of the classroom environment and its relation to classroom discipline from the view point of teachers in the second cycle schools of basic education in Lattakia city, and to identify the relationship between the Classroom Environment and Classroom Discipline, the research also aimed at deciphering the impact of variables such as (sex, qualification, region of education).The research used the descriptive analytical approach, and to achieve the objectives of the research, questionnaire has been included two axises (classroom environment: 30 items and classroom control 28 items), were applied on sample (202) teachers in the second cycle schools of basic education in Lattakia city during the academic year of (2019 - 2020). Validity of the questionnaire was established though a number (7) of the teaching staff of faculty at Tishreen and Tartous Universities. Pilot sample consisted of (30) teachers, Reliability was established through Cronbach – Alpha (0.91) for first axis, and (0.887) for second axis, which indicate to high Reliability to questionnaire. The research revealed the following result, the degree of the second cycle schools of basic education in Lattakia city recognition for the reality of the classroom environment was middle, whereas their recognition to students’classroom discipline was middle degree. The research cleared positive correlation was found between the classroom environment and classroom discipline from the view point of teachers. The research also revealed that there are no found differences in the degree of recognition of teachers to reality of the classroom environment related to (sex, qualification, region of education). In Addition to no significant differences were found in the degree of recognition of teachers to students’classroom discipline related to (sex, region of education), while there are found differences in the degree it's found according to the variable (qualification), in favor of the education preparation diploma. The research recommended availability of resources and attractive classrooms, and organize courses for teachers in the field of psychological and educational guidance to students.